Evaluation of modifiable factors and polygenic risk score in thyroid cancer. Issue 7 (17th June 2021) - Hoang, Tung; Nguyen Ngoc, Quy; Lee, Jeonghee; Lee, Eun Kyung; Hwangbo, Yul; Kim, Jeongseon
Abstract : The cumulative effect of single-nucleotide polymorphisms (SNPs) on thyroid cancer has been adequately defined in individuals of European ancestry; however, similar evidence in the Korean population is limited. This study aimed to investigate the influence of modifiable factors and the polygenic risk score (PRS) and their interactive and combined effects on thyroid cancer. Using data from the cancer screenee cohort, this study included 759 thyroid cancer cases and 759 age- and sex-matched controls. We examined the effects of tobacco smoking, alcohol consumption, and regular exercise habits, BMI, and the PRS of six SNPs on thyroid cancer. Odds ratios (ORs) and 95% confidence intervals (CIs) for the associations were obtained using a conditional logistic regression model. The results indicated that family history, obesity, and the unweighted and weighted PRS were independently associated with susceptibility to thyroid cancer, with ORs (95% CIs) of 2.96 (1.63–5.36), 1.72 (1.20–2.48), 1.46 (1.10–1.93), and 1.56 (1.19–2.03), respectively, whereas the effect of smoking, drinking, and regular exercise was not significant. The contribution of the PRS remained after stratifying participants with healthy behaviors, such as nonsmokers/nondrinkers, and regular exercise. Although the PRS did not significantly contribute to the risk for thyroid cancer when participants were stratified according to BMI, BMI and the PRS had a cumulative effect on thyroid cancer risk. The combined effect of genetic polymorphisms on predisposition to thyroid cancer may differ based on tobacco smoking, alcohol consumption, regular exercise behaviors and cumulative BMI. Larger population-based studies are needed to validate these findings.